Association of Metabolic Syndrome with Increased Cardiovascular Risk in Hypothyroidism Patients: Evidence from a Nepalese Population - Jha, Bipin Kumar; Lamichhane, Anit; Shrestha, Saguna Laxmi Tandukar; Maharjan, Sabindra; Joshi, Govardhan; Adhikari, Nitesh; Khadka, Anil; Bista, Pabitra; Thakur, Rajesh Kumar; Khanal, Sudip; Gautam, Sujan; Acharya, Aashish; et al. (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Hypothyroidism is associated with metabolic syndrome and increased cardiovascular disease (CVD) risk worldwide. This study is conducted to assess hs-CRP as a CVD risk marker in hypothyroidism patients with and without metabolic syndrome. Method: A cross-sectional study was conducted at Manmohan Memorial Teaching Hospital, Kathmandu, Nepal involving 244 participants where 122 euthyroid controls and 122 with hypothyroidism cases. Anthropometric data, blood pressure, fasting glucose, lipid profile, thyroid hormones, and hs-CRP were analyzed. Results: Individual with hypothyroidism showed significantly increased level of DBP, WC, FBS, TC, TG, LDL, and hs-CRP, and lower HDL levels (p<0.001) as compared to euthyroid controls. Level of hs-CRP showed positive and significant correlation with SBP, DBP, TC, and LDL whereas negative and significant correlation with HDL. The incidence of MetS among primary hypothyroidism was 28% and 15.8% among sub clinical hypothyroidism. SBP (p<0.001), DBP (p<0.001), WC (p<0.001), FBS (p<0.001), TG (p<0.001), TC (p<0.001), and hs-CRP were significantly (p<0.01) higher among hypothyroidism cases with MetS as compared to hypothyroidism without MetS. Similarly HDL (p<0.01) was significantly lower in hypothyroidism cases with MetS as compared to hypothyroidism without MetS. Hypothyroidism cases with MetS were more prone to CVD risk as compared to the cases without MetS where majority (60%) of them were under high CVD risk followed by intermediate (28%) and low risk (12%). Conclusion: Significant elevation of hs-CRP in hypothyroidism with metabolic syndrome shows higher CVD risk as compared to hypothyroidism without MetS which revealed that MetS exacerbate CVD risk in hypothyroidism cases. hs-CRP can also be a useful screening marker for CVD risk management.